Trajectories of forced vital capacity in patients with systemic sclerosis-associated interstitial lung disease - Oliver Distler; Madelon C Vonk; Arata Azuma; Maureen D. Mayes; Dinesh Khanna; Kristin B. Highland; Gerrit Toenges; Margarida Alves; Yannick Allanore (Arthritis Research & Therapy)
Abstract We used data from the SENSCIS and SENSCIS-ON trials to assess decline in forced vital capacity (FVC) in patients with systemic sclerosis-associated interstitial lung disease (SSc-ILD) who received long-term treatment with nintedanib and the effect of switching patients from placebo to nintedanib. In the SENSCIS trial, patients were randomised to receive nintedanib or placebo until the last patient reached week 52 but for ≤ 100 weeks. In SENSCIS-ON, the extension to SENSCIS, all patients received open-label nintedanib. Per protocol, the off-treatment period between these trials was ≤ 12 weeks. We assessed the trajectory of FVC in patients who received nintedanib in SENSCIS and continued nintedanib in SENSCIS-ON (n = 197) and in patients who received placebo in SENSCIS and initiated nintedanib in SENSCIS-ON (n = 231). The last on-treatment measurement in SENSCIS and the baseline measurement of SENSCIS-ON were considered anchor measurements. In patients who received nintedanib in SENSCIS, the mean decline in FVC in the 52 weeks prior to the last on-treatment measurement in SENSCIS was − 41.5 mL and the mean decline in FVC from baseline to week 52 of SENSCIS-ON was − 58.3 mL. In patients who received placebo in SENSCIS, the mean decline in FVC in the 52 weeks prior to the last on-treatment measurement in SENSCIS was − 96.8 mL and the mean decline in FVC from baseline to week 52 of SENSCIS-ON (when patients received nintedanib) was − 42.8 mL. These findings illustrate the progressive nature of SSc-ILD and support the efficacy of nintedanib in slowing decline in lung function over the long term.